PROBLEMATIKA JATUH CINTA : Sebuah Tinjuan Filosofis - Gunawan, Leo Agung Srie (LOGOS, 2018)
Falling in love is the most phenomenal event in the history of human being.Discussion of falling in love is never finished talking about it. When lovers arefalling in love, they long for a perfect happiness in their heart. The onlypossibility to achieve this happiness is that the lovers live together as amanifestation of the unity of love. This union that is lived by them is expectedto take place in eternity. In the experience of falling in love, a couple of humanbeing, as if, live â€œacross this worldâ€ in which they are tasting the divine life intotal happiness, perfect unity, and eternal life. Actually, the total happiness isexperienced as a partial happiness. This has the effect that the perfect unity isonly a dream because the unity is experienced in its imperfection. Furthermore,the eternity of love is only a romantic love in changing continuously. It is theexperience bringing falling in love with its serious problems. However, thosewho fall in love are really human beings who are still in their limitations.